Women's collectives as champions of climate-smart agriculture and water resilience - AI-Zu'bi, Maha; Krishna, Vijesh (2024)
On International Rural Women's Day, the International Water Management Institute and the International Maize and Wheat Improvement Center {CIMMYT) celebrate the vital role women play in shaping sustainable water, land, and food systems, especially in rural regions facing resource challenges. Supported by the CGIAR Gender Platform, the two centers implement the "Learning in Tandem" project, which highlights the transformative power of women's collectives across the Middle East and North Africa and South Asia. These collectives are driving gender equity and fostering resilience in agriculture by managing water resources, enhancing land productivity and ensuring food security. In Morocco and India, these collectives have adopted climate-smart farming practices, promoted water conservation and empowered women economically and socially. Their efforts highlight the importance of local leadership in building climate resilience and sustainable agricultural development, providing a blueprint for communities globally.